Dampak Stres DAMPAK STRES PADA ANAK DALAM PERKEMBANGAN OTAK ANAK - Muthi’ah Jihadillah Saepurohman; Najmu Hawa; Debie Susanti (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
Stress in children is a trauma that can hinder and even damage the development of a child's brain. When a child is under pressure, whether light or heavy from an incident that is intentional or not, it can affect the child's brain development. Therefore, children should be avoided as much as possible so as not to get events that make them traumatized which later when they occur in the long term and continuously can cause children to become stressed. As we know the brain is an important thing in human life, because the brain is said to be the center of everything that the human will do in the future. By avoiding excessive stress on children and providing a good stimulus is the same as making a child's brain development good and very good. Of course, it will produce good results in the future.